An Insight On Phoenix Sylvestris Synthesized Agnps For Its Potential As Antimicrobial Agent And Wastewater Management - Rao, Reddi Papa; Acharya, D.K.; Swapnavahini, K.; Matha, Sumanth Kumar (Journal of Neonatal Surgery, 2025)
The emphasis of nanobiotechnology is on the environmentally benign creation of nanoparticles utilizing living creatures, such as bacteria, plant extracts, or plant biomass. Plants are among the many agents utilized in the synthesis of nanoparticles, and they have major applications. Plant-derived biomolecules cause Ag+ ions to be reduced from silver nitrate to silver nanoparticles (AgNPs). In the current study, aqueous leaf extract from Phoenix sylvestris was utilized as a stabilizing and reducing agent during the manufacture of silver nanoparticles. The production of silver nanoparticles is shown by a color shift from translucent yellow to dark brown, indicating the confirmation of the synthesized nanoparticle. Utilizing UV-Vis absorption spectroscopy, the quantitative production of silver nanoparticles was observed. The generated AgNPs' Surface Plasmon Resonance was measured at 462 nm.The gram positive and gram negative bacteria were used in the antimicrobial tests. The results showed that the zone of inhibition of the produced silver nanoparticles was 20.52 mm for Staphylococcus aureus, 21.54 mm for Proteus vulgare, 20.37 mm for Klebsiella pneumoniae, and 21.86 mm for Bacillus subtilis. Using the leaf extract from P.sylvestris, the removal capacities for [Cr (VI)], [Fe (III)], and [Mn (II)] were found to be 41.6%, 42.4% and 3.3%, respectively. This demonstrates the stimulatory nature of AgNPs towards the removal of heavy metals from wastewaters. Thus it may be considered that the plant-based approach is a safe, affordable, and ecologically beneficial biological way to produce silver nanoparticles.